Obstacle avoidance under strict path following - Rosendo, Juan Luis (2017)
In this work an obstacle avoidance technique for strict path following task of robotic systems is proposed and tested through simulations. The main idea is to implement an speed adaption loop which based on a discontinuous signal product of an sliding surface in the state space, modifies the speed of reference for a robot. The strength of this approach is that we solve, under certain conditions, the problem of obstacle avoidance when it is forbidden for the robot to leave the given path. Furthermore, we are able to impose a robust desired dynamics in the approach between the robot and the obstacle.